Mycobacterium tuberculosis and Paracoccidioides brasiliensis Formation and Treatment of Mixed Biofilm In Vitro - Medina-Alarcón, Kaila Petronila; Tobias da Silva, Iara Pengo; Ferin, Giovana Garcia; Pereira-da-Silva, Marcelo A.; Marcos, Caroline Maria; dos Santos, Mariana Bastos; Regasini, Luis Octávio; Chorilli, Marlus; Mendes-Giannini, Maria José S.; Pavan, Fernando Rogerio; Fusco-Almeida, Ana Marisa (Frontiers in Cellular and Infection Microbiology, 2021)
Co-infection of Mycobacterium tuberculosis and Paracoccidioides brasiliensis, present in 20% in Latin America, is a public health problem due to a lack of adequate diagnosis. These microorganisms are capable of forming biofilms, mainly in immunocompromised patients, which can lead to death due to the lack of effective treatment for both diseases. The present research aims to show for the first time the formation of mixed biofilms of M. tuberculosis and P. brasiliensis (Pb18) in vitro, as well as to evaluate the action of 3’hydroxychalcone (3’chalc) -loaded nanoemulsion (NE) (NE3’chalc) against monospecies and mixed biofilms, the formation of mixed biofilms of M. tuberculosis H37Rv (ATCC 27294), 40Rv (clinical strains) and P. brasiliensis (Pb18) (ATCC 32069), and the first condition of formation (H37Rv +Pb18) and (40Rv + Pb18) and second condition of formation (Pb18 + H37Rv) with 45 days of total formation time under both conditions. The results of mixed biofilms (H37Rv + Pb18) and (40Rv + Pb18), showed an organized network of M. tuberculosis bacilli in which P. brasiliensis yeasts are connected with a highly extracellular polysaccharide matrix. The (Pb18 + H37Rv) showed a dense biofilm with an apparent predominance of P. brasiliensis and fragments of M. tuberculosis. PCR assays confirmed the presence of the microorganisms involved in this formation. The characterization of NE and NE3’chalc displayed sizes from 145.00 ± 1.05 and 151.25 ± 0.60, a polydispersity index (PDI) from 0.20± 0.01 to 0.16± 0.01, and zeta potential -58.20 ± 0.92 mV and -56.10 ± 0.71 mV, respectively. The atomic force microscopy (AFM) results showed lamellar structures characteristic of NE. The minimum inhibitory concentration (MIC) values of 3’hidroxychalcone (3’chalc) range from 0.97- 7.8 µg/mL and NE3’chalc from 0.24 - 3.9 µg/mL improved the antibacterial activity when compared with 3’chalc-free, no cytotoxicity. Antibiofilm assays proved the efficacy of 3’chalc-free incorporation in NE. These findings contribute to a greater understanding of the formation of M. tuberculosis and P. brasiliensis in the mixed biofilm. In addition, the findings present a new possible NE3’chalc treatment alternative for the mixed biofilms of these microorganisms, with a high degree of relevance due to the lack of other treatments for these comorbidities.